Zinc Amido-Oxazolinate Catalyzed Ring Opening Copolymerization and Terpolymerization of Maleic Anhydride and Epoxides - Muneer Shaik; Vamshi K. Chidara; Srinivas Abbina; Guodong Du (Molecules, 2020)
Ring opening copolymerization (ROCOP) of epoxides and cyclic anhydrides has become an attractive approach for the synthesis of biodegradable polyesters with various compositions. Encouraged by the efficiency and versatility of a series of amido-oxazolinate zinc complexes, in this study they were shown to be active catalysts for the synthesis of unsaturated polyesters via ROCOP of maleic anhydride and various epoxides. The relative activity of epoxides in these reactions was observed to be styrene oxide > cyclohexene oxide > phenyl glycidyl ether, which could be correlated with the electronic and steric features of the substrate. To provide more structural possibilities for the polyesters, the difference in epoxide reactivity was exploited in an attempt to prepare block terpolymers from one anhydride and two epoxides. Terpolymerization was carried out in one or two steps in a single pot. The thermal characterization by thermogravimetric analysis (TGA) and differential scanning calorimetry (DSC) techniques suggested that the resulting materials were mostly random terpolymers.